High-Field Growth of Semiconducting Anodic Oxide Films on Metal Surfaces for Photocatalytic Application - Ronald Vargas; David Carvajal; Brunella Galavis; Alberto Maimone; Lorean Madriz; Benjamín R. Scharifker (International Journal of Photoenergy)
This work summarizes progresses achieved in the physical chemistry aspects of the growth of anodic oxides under high-field conditions for the synthesis of semiconducting thin solid films and their implementation as photocatalytic materials. We discuss the scope and mechanisms for anodic oxide growth, describing the development of kinetic models and the correlations between theory and kinetic data, leading to fundamental information to characterize the primary processes occurring during the anodization of valve metals under high fields. The main features related to the widely used self-assembly of nanostructures by valve metal anodization are highlighted and briefly discussed. This is followed by general considerations of heterogeneous photocatalysis on these functional materials, considering the kinetics of the heterogeneous catalytic processes involved and the overall photoelectrochemical performance. High control of the characteristics of the materials obtained with the method described, combined with the possibility of electrochemically assisting photocatalysis, allows application of this technology to the treatment of wastewaters, energy conversion, and related fields.